Multi-directional deformation for coordinating isotropy and strength-ductility synergy in a CoCrNi alloy - Na Lin; Zhicheng Miao; Mingcan Li; Rumeng Huang; Kaiyuan Zheng; Zhaowen Huang; Donghui Wen; Cong Zhang; Anding Wang (Journal of Materials Research and Technology)
Due to the intrinsic lattice symmetry, anisotropy always exists in metallic materials, and it will be further enhanced or reduced to a certain degree during the subsequent processing, leading to the directional strength-ductility modulation. To meet the high-performance requirements for complicated servicing environments, the isotropy should always be coordinated. In this study, an equ-atomic CoCrNi alloy with significant work hardening ability yet extraordinary processability was selected as a model material, and rotary rolling (RR) and unidirectional rolling (UR) were employed to modulate the deformation isotropy. It is found that the RR-ed sample achieves an exceptional strength-ductility combination with strength of 1569 ± 16 MPa and uniform elongation of 8.8± 0.1 %. Moreover, the ultimate tensile strength fluctuation of the RR-ed sample is smaller than 30 MPa (1.9 %) when the tensile angle ranges from 0° to 90 °, showing much better homogeneity compared to the UR counterpart (183 MPa, 11.1 %). This unique mechanical property isotropy is ascribed to the relatively uniform in-plane microstructure distribution, as well as the analogous cracking behavior along different directions. These results might provide a new strategy and basic theory for achieving high performances in multi-direction by machining advanced structure materials.